1998
DOI: 10.1029/98ja01740
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic theory of wave‐particle resonant diffusion with application to electron acceleration in the magnetosphere

Abstract: Abstract.Resonant diffusion curves for electron cyclotron resonance with field-aligned electromagnetic R mode and L mode electromagnetic ion cyclotron (EMIC) waves are constructed using a fully relativistic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
847
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 790 publications
(886 citation statements)
references
References 39 publications
21
847
1
2
Order By: Relevance
“…Theoretical calculations suggest that ULF acceleration mechanisms should be substantially reduced in efficiency at lower L, compared to geosynchronous orbit (Fälthammar and Walt 1969;Elkington et al 2003). On the other hand, local acceleration involving VLF waves, particularly lower-band chorus, becomes most efficient in the region just outside the plasmapause, which corresponds to the radial range 3-5 RE for storm conditions (Summers et al 1998;Meredith et al 2003b).…”
Section: Which Physical Processes Produce Radiation Belt Enhancement mentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical calculations suggest that ULF acceleration mechanisms should be substantially reduced in efficiency at lower L, compared to geosynchronous orbit (Fälthammar and Walt 1969;Elkington et al 2003). On the other hand, local acceleration involving VLF waves, particularly lower-band chorus, becomes most efficient in the region just outside the plasmapause, which corresponds to the radial range 3-5 RE for storm conditions (Summers et al 1998;Meredith et al 2003b).…”
Section: Which Physical Processes Produce Radiation Belt Enhancement mentioning
confidence: 99%
“…Since the power in ULF waves is considerably enhanced during magnetic storms (Mathie and Mann 2000), radial diffusion is a potentially important mechanism for energetic electron acceleration (Rostoker et al 1998;Elkington et al 1999;Hudson et al 2001;O'Brien et al 2001;Shprits and Thorne 2004) or loss (Shprits et al 2006;Jordanova et al 2008;) during storm conditions, dependent on the radial gradient in phase space density. Higher frequency ELF and VLF waves cause violation of the first two invariants and lead to pitch angle scattering loss to the atmosphere (Thorne and Kennel 1971;Lyons et al 1972;Thorne 1998a, 1998b) or local stochastic energy diffusion (Horne and Thorne 1998;Summers et al 1998;Miyoshi et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These waves have been shown to be very important in both the acceleration [e.g., Summers et al, 1998;Horne et al, 2005a] and the precipitation [Thorne et al, 2005] of relativistic radiation belt electrons. Chorus waves have also been demonstrated to be the dominant wave mode for scattering plasma sheet electrons into the atmosphere to form the diffuse aurora [Thorne et al, 2010], the pulsating aurora [Nishimura et al, 2010] and to create the pitch angle distributions of energetic electrons observed in the inner magnetosphere [Tao et al, 2011a].…”
Section: Introductionmentioning
confidence: 99%
“…What is actually happening is the HILDCAAs are related to sporadic, low-intensity particle injections into the outer portions of the ringcurrent, thus the lack of an overall "decay" . The continuous presence of magnetospheric chorus plasma waves (and other wave modes) associated with HILDCAAs has been invoked (Horne and Thorne, 1998;Summers et al, 1998; to explain the magnetospheric relativistic electron events (Baker et al, 1989;Li et al, 1997) present in these intervals of high-speed solar wind streams. These relativistic electrons have been related to the possible failure of a Canadian telecommunication satellite.…”
Section: Hildcaasmentioning
confidence: 99%